Analysis of nonlinear characteristics of a graphene based four-terminal ballistic rectifier using a drift-diffusion model. Issue 10 (24th September 2019) - Garg, Ankur; Jain, Neelu; Kumar, Sanjeev; Kasjoo, Shahrir R.; Singh, Arun Kumar
Abstract : In this study, rectification behavior and noise spectra of a graphene based four-terminal ballistic rectifier are reported utilizing semi-classical drift-diffusion 3D modeling. Abstract : In this study, rectification behavior and noise spectra of a graphene based four-terminal ballistic rectifier are reported utilizing semi-classical drift-diffusion 3D modeling. The room temperature DC and RF characteristics of the novel rectifier are demonstrated considering the traps in the material similar to a real device, reducing the rectification efficiency from 0.5% to 0.35%. The responsivity and noise equivalent power of about 89.21 mV mW −1 and 97.52 pW Hz −1/2, respectively, are obtained for different frequencies varying from 50 Hz to 1 THz. Furthermore, the noise spectral analysis of the device predicts a minimum low frequency noise, which depends upon the carrier concentration inside the device active region rather than mobility, and hence enables potential applications as THz detectors for imaging.